The Water-Energy-Food Nexus Index: A Tool to Support Integrated Resource Planning, Management and Security - Simpson, Gareth B.; Jewitt, Graham P. W.; Becker, William; Badenhorst, Jessica; Masia, Sara; Neves, Ana R.; Rovira, Pere; Pascual, Victor (Frontiers in Water, 2022)
The call for measuring synergies and trade-offs between water, energy, and food is increasing worldwide. This paper presents the development and application of a country-level index that has been calculated for 181 nations using open databases. Following an assessment of 87 water-, energy- and food-related indicators, 21 were selected to constitute the Water-Energy-Food (WEF) Nexus Index. In this paper, the WEF Nexus Index is utilized to assess the Southern African Development Community, where it demonstrates that food security is an area of concern, while the potential for beneficially exploiting water resources and energy projects exists in several countries. Water for agriculture could be achieved through the drought-proofing of rainfed agriculture and systematic irrigation development, with energy as the critical enabler. Neither the composite indicator nor the WEF nexus approach is the panacea that will solve all the significant development or environmental challenges facing humanity. However, they could contribute to integrated resource management and policy-making and are complementary to the Sustainable Development Goals. In this study, the methodology set out by the Joint Research Centre's Competence Centre on Composite Indicators and Scoreboards has been followed.